What drives remittances during a global shock? evidence from the COVID-19 pandemic in Mexico - Ambrosius, Christian; Campos-Vázquez, Raymundo M.; Esquivel, Gerardo (Freie Universität Berlin, 2021)
During a global shock two forces act upon international remittances in opposite directions: income losses among migrants may reduce their ability to send remittances and, at the same time, migrants' concern for their family's wellbeing may prompt them to send more remittances back home. Which of these drivers prevail is an empirical matter. We assemble quarterly data at the subnational level in Mexico to study the behavior of remittances during the Covid-19 pandemic. We estimate elasticities of remittances with respect to employment conditions at both origin and destination places of Mexican migrants. Our results show that destination country conditions have been the main driver of remittances to Mexico, whereas origin country conditions had no discernible effect on remittances during the pandemic. We also show that contractions in consumption in Mexico are associated with reductions in remittances. We conclude that risk-coping via remittances provides limited protection during global crises
Keywords: Geschichte 2019-2021; Migration; COVID-19; Remittances; Consumption; Mexico; Pandemie; Überweisung; Auswanderer; Herkunftsland; Soziale Situation; Mexiko